Dosimetric considerations from 200 prostate brachytherapy treatments with 1251 according to the real-time planning method - Teixeira, Nuno (2018)
Prostate brachytherapy with radioactive seeds is one of the options for prostate cancer treatment. Some dosimetric methods may be used, from the pre-planning to the realtime planning. This study covers 200 patients treated with 12sI radioactive seeds, for a period of time of 4 years. The software used is VariSeed. According to the real-time planning method, the dosimetry is done inside the operating room. The ultrasound probe is inside the rectum of the patient during all the treatment time, and images of the prostate, urethra and rectum are obtained by ultrasound technique. The dosimetry is on realtime, and the source positions in the TPS are exactly the same of the positions inside the prostate. With this technique one may have the values of very important parameters, like Dgo Dgs Vgo Dloo and Vlso for prostate. After one month the patient is submitted to a CT exam, and a new dosimetry is performed, being the contouring done over the new C-I images. With this new dosimetry one may calculate the same parameters already calculated for the real-time planning dosimetry. In this work authors present a statistical analysis (table 1) of the main parameters, obtained either duringthe pre-planning dosimetry or from the CT, and show some very interesting results and conclusions.